Reflections on Bioethics 2018
DOI: 10.5772/intechopen.74519
|View full text |Cite
|
Sign up to set email alerts
|

Bioethics in Education

Abstract: In dynamic ambits, systems have to be maintained in a constant process of adaptation. Thus, in the present chapter, we explore the integration of bioethics in all areas of higher education (physics-mathematics, the engineering sciences, social and administrative sciences, the biological-medical sciences, and the humanities), with the objective of establishing, as an essential part, bioethics in all disciplines of knowledge. All undergraduate university degrees converge in the relation among living beings, thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These principles anchor on andragogy which is characterised by the use of self-direction, transformation, experience, mentorship, mental orientation, motivation, and readiness to learn (Gouthro, 2019). Andragogy has proven as the most appropriate methodology for teaching bioethics which ensures that students are motivated to learn, are able to relate to past experiences in the area of interest, and are eventually able to make moral judgments from their environment and current situations they experience (Morales-González et al, 2018). This is evident from the research training that was undertaken which showed that effective learning was achieved through the use of experiential learning, where participants were able to share experiences from the past research undertaken and relate it to the subject of discussion during the sessions.…”
Section: Discussionmentioning
confidence: 99%
“…These principles anchor on andragogy which is characterised by the use of self-direction, transformation, experience, mentorship, mental orientation, motivation, and readiness to learn (Gouthro, 2019). Andragogy has proven as the most appropriate methodology for teaching bioethics which ensures that students are motivated to learn, are able to relate to past experiences in the area of interest, and are eventually able to make moral judgments from their environment and current situations they experience (Morales-González et al, 2018). This is evident from the research training that was undertaken which showed that effective learning was achieved through the use of experiential learning, where participants were able to share experiences from the past research undertaken and relate it to the subject of discussion during the sessions.…”
Section: Discussionmentioning
confidence: 99%
“…With particular insights and influences from various philosophies, all theories of biomedical ethics try to arrive at the best way to honorably and justly treat patients [13]. Recent research suggests the study of bioethics would benefit from methodological study from all perspectives, whether bioscience or the humanities, as the patient in which it seeks to serve may be influenced by more worldviews than one [14].…”
Section: The Lingua Franca Of Bioethicsmentioning
confidence: 99%
“…As language, ethics, and cognition are inherently intertwined [16], there is a need to study all forms of communicative value [including that of the orthonym] from various perspectives including bioethics [14]. Communication between clinics Biomedical Ethics and Communicative Maxims: Case Studies in Outpatient Health DOI: http://dx.doi.org /10.5772/intechopen.93233 and communities must respect and abide by ethical institutions to do no harm [17].…”
Section: Communication In Healthcarementioning
confidence: 99%
“…In October 1996, in its Fourth Session, the IBC prepared an information document on the topic "Bioethics and Women," to give visibility to a theme that was already vigorous at the time and that required more considerable attention (UNESCO 1996). At this meeting, bioethics, as an institution, formalized its recognition in the face of the pressing need for a more in-depth study on gender equality, from the perspective of human rights and within the scope of its field of action (Lorraine 2001).…”
Section: Bioethical Approach Related To Gender Equalitymentioning
confidence: 99%